Effect of single-injection thoracic paravertebral block with liposomal bupivacaine on the quality of recovery after thoracic surgery: a protocol for an open-label, randomized controlled trial - Ma, Wenru; Wang, Li; Zhang, Haiping; Zou, Meijia; Feng, Shiran; Liu, Yinhuan; Wang, Peng (Frontiers in Medicine, 2026)
BackgroundPostoperative pain management plays a crucial role in determining the quality of recovery following thoracic surgery. However, achieving high-quality postoperative analgesia that facilitates satisfactory recovery remains challenging due to suboptimal pain control and side effects associated with conventional analgesic strategies. This study aims to evaluate the effect of single-injection thoracic paravertebral block with liposomal bupivacaine on the overall quality of recovery in patients undergoing thoracic surgery.MethodsThis single-center, open-label, randomized controlled trial will enroll 162 patients scheduled for video-assisted thoracic surgery. Participants will be randomly allocated in a 1:1:1 ratio to three groups (n = 54 each): Group L will receive ultrasound-guided thoracic paravertebral block with liposomal bupivacaine; Group R will receive ropivacaine-based paravertebral block combined with opioid-based patient-controlled intravenous analgesia; and Group P will receive opioid-based patient-controlled intravenous analgesia alone. The primary outcome is the quality of recovery assessed by patient-reported Quality of Recovery-15 scores on postoperative days 1–3. Between-group differences will be analyzed using generalized estimating equations. Secondary outcomes include: pain-free interval; resting and cough-induced pain intensity at 6, 12, 24, 48, and 72 h; worst pain scores at 24, 48, and 72 h; perioperative opioid use; time to first rescue analgesia and times of request; patient confidence in coughing and ambulation; anxiety and sleep quality at 24, 48, and 72 h; patient satisfaction; postoperative nausea and vomiting incidence/severity and rescue antiemetic use. Safety outcomes comprise block-related complications and postoperative complications. All adverse events will be documented throughout the study.DiscussionThis study aims to provide high-quality evidence on the efficacy of a single-injection thoracic paravertebral block with liposomal bupivacaine for post-thoracic surgery analgesia, compared with opioid-based intravenous analgesia alone and the combination of ropivacaine paravertebral block with systemic opioid analgesia.Clinical trial registrationIdentifier: ChiCTR2500107787.